Challenges faced by chinese women entrepreneurs in Batu Pahat, Johor - Jusoh, Nur Aniza Quantaniah; Wan Yusoff, Wan Fauziah; Kepal, Noreina; Han, Pau Yu (American Scientific Publishers, 2018)
Entrepreneurship is today considered to be a relevant vehicle for economic development and women contribute to it significantly worldwide. Women represent half of the total population in Malaysia and the contribution of them towards the economic development of the country has long been recognized. However, the participation rate of women in entrepreneurship were still low and have not achieved a satisfied level in Malaysia. Entrepreneurial women face challenges inherent to their multifaceted livelihoods and also face structural barriers which have limited their growth and progress in their business ventures. Malaysia is a multi-ethnic nation, with three main ethnic groups—the Malay, the Chinese and the Indian. However, this research only focused on the Chinese women entrepreneur in one of the district in Johor, a state in the southern region of Malaysia. The main aim was to identify the challenges faced by Chinese women entrepreneurs in their business venture. The study used a purposive sample comprising 40 Chinese women entrepreneurs in Batu Pahat, Johor. The study examined variables such as finance, family, knowledge and skills, market and competition, social networking and risk taking that may be challenges to the Chinese women entrepreneur. The findings reveal that the main challenge faced by Chinese women entrepreneurs in Batu Pahat, Johor was finance related challenge such as the inabilities to obtain financial loans, dependent on personal savings, lack of finance assistance given by government agencies to women entrepreneurs complicated procedures to apply bank loans and high loan repayment rates.